The SUMO E3 Ligase MdSIZ1 Sumoylates a Cell Number Regulator MdCNR8 to Control Organ Size - Wang, Gui-Luan; Zhang, Chun-Ling; Huo, He-Qiang; Sun, Xiao-Shuai; Zhang, Ya-Li; Hao, Yu-Jin; You, Chun-Xiang (Frontiers in Plant Science, 2022)
Plant growth and organ size putatively associated with crop yield are regulated by a complex network of genes including ones for controlling cell proliferation. The gene fw2.2 was first identified in tomato and reported to govern fruit size variation through controlling cell division. In this study, we isolated a putative ortholog of the tomato fw2.2 gene from apple, Cell Number Regulator 8 (MdCNR8). Our functional analysis showed that MdCNR8 may control fruit size and root growth. MdCNR8 was mediated by the SUMO E3 ligase MdSIZ1, and sumoylation of MdCNR8 at residue-Lys39 promoted the translocation of MdCNR8 from plasma membrane to the nucleus. The effect of MdCNR8 in inhibiting root elongation could be completely counteracted by coexpression of MdSIZ1. Moreover, the lower cell proliferation of apple calli due to silencing MdSIZ1 could be rescued by silencing MdCNR8. Collectively, our results showed that the MdSIZ1-mediated sumoylation is required for the fulfilment of MdCNR8 in regulating cell proliferation to control plant organ size. This regulatory interaction between MdSIZ1 and MdCNR8 will facilitate understanding the mechanism underlying the regulation of organ size.